PENGARUH PENAMBAHAN ALKANOLAMIDA TERHADAP KARAKTERISTIK PEMATANGAN DAN KEKERASAN VULKANISAT KARET ALAM BERPENGISI SILIKA - Harry Laksana Tampubolon, Darwis Syarifuddin Hutapea, Indra Surya (Jurnal Teknik Kimia USU, 2012)
By using a semi-efficient sulfur accelerated vulcanization system, a research about the effect of  the alcanolamide on cure characteristics and hardnes propertiess of natural rubber filled silika and alkanolamide been done. Alcanolamide produced from palm oil derivatives reacted with dietanolamine. Alcanolamide aaded  into  rubber  with levels 1.0, 3.0; 5.0; 7.0; 9.0; phr. It was found that  alcanolamide gave shorter  Scorch time and cure time. Alkanolamide also exhibited higher torque different, tensile moduli, tensile strength, and crosslink density up to  5.0 phr and ten decrease with future increaseing addition of alcanolamide.Keywords: alcanolamide, cure time, Scorch time, crosslink density, vulcanizate natural rubber